The Implications of Girl-Child Education to Nation Building in the 21st Century in Nigeria (Global Journal of Human-Social Science, 2016)
This paper examines the implications of Girl-child to nation building in the 21 st century in Nigeria. The paper began by pointing out the wrong notions that many Nigerians have particularly the rural dwellers about women being consider as properties for man and objects for their pleasure and how this notion restrains them from training their girl-children in schools. The paper further examined the concept of girl-child education to be all inclusive, some hindrances to effective girl-child education such as economic factors, sexual violence and abuse, political factors, the school environmental factors and socio-cultural and religious factors were highlighted. Included in the paper also was the implications that effective girl-child education would have on nation building such as poverty-reducing effects, improves health and nutrition, reduces inequality, reduces women's fertility rates, lowers infant and mortality rates and increases women's labour force participation rates and earnings.
Keywords: girl-child; education; implication; nation; building; 21st century Nigeria